Psychometric Evaluation of the Parental Reflective Functioning Questionnaire in Chinese Parents - Ye, Panqin; Ju, Jiawen; Zheng, Kejun; Dang, Junhua; Bian, Yufang (Frontiers in Psychology, 2022)
Parental reflective functioning (PRF) is important for parenting and child development. To effectively assess PRF in Chinese parents, this study aimed to revise the Parental Reflective Functioning Questionnaire (PRFQ) for the Chinese context. The original Chinese version of the PRFQ (PRFQ-C) was revised by following psychometric validation procedures in a sample of Chinese parents (N = 2,021, 1,034 mothers and 987 fathers). A series of psychometric analyses, including confirmatory factor analysis (CFA), internal consistency reliability analysis, discriminant validity, and criterion-related validity analysis, and analysis for measurement invariance between mothers and fathers, were conducted. The CFA results indicated that the final 12-item, three-factor model had a good fit χ2(49) = 472.381; CFI = 0.929; TLI = 0.904; RMSEA = 0.065, 90%CI = [0.060, 0.071]. The Chinese version of the PRFQ with 12 items (PRFQ-12C) showed satisfactory reliability (omega = 0.68–0.82), discriminant validity [heterotrait-monotrait (HTMT) values < 0.85], and criterion-related validity. The PRFQ-12C also had measurement invariance across mothers and fathers. In conclusion, the PRFQ-12C is psychometrically sound and can be applied in China.